Electron partitioning in soluble organic products by wild-type and modified Synechocystis sp. PCC 6803. (July 2016) - Nguyen, Binh T.; Rittmann, Bruce E.
Abstract: The partitioning of electrons photosynthetically fixed in carbon by the cyanobacterium Synechocystis sp. PCC 6803 was evaluated for up to 24-day batch cultures continuously exposed to incident light intensity (LI) from 111 to 598 μEm −2 s −1 . The fate of fixed electrons was assayed by Chemical Oxygen Demand (COD) in biomass, generic soluble microbial products (SMP), and excreted laurate (for a modified strain). Because SMP is not a valuable product, light energy embedded in SMP is wasted. Normalized to the total COD (TCOD), wild-type Synechocystis partitioned 75–84% of its TCOD in particulate biomass and 16–25% in generic SMP. A strain modified to excrete lauric acid partitioned 6.6%–10% of its TCOD in laurate, 21%–30% in generic SMP, and 64%–69% in particulate biomass. The greatest electron partitioning in SMP occurred with the highest LI tested, which suggests that moderating the LI in the photobioreactor is a promising mean to accentuate the production of valuable forms of photosynthetically fixed electrons. Graphical abstract: Highlights: SMP are non-useful sinks for electrons fixed through photosynthesis. Of its total photosynthetically fixed electrons, 16%–30% embedded in generic SMP. And 64%–84% embedded in particulate biomass by Synechocystis sp. PCC 6803. Releasing less SMP increases productivity of particulate biomass and valued product.